Experimental determination and mathematical modelling of residence time distributions by using pieces of urban art - Salmi, Tapio; Tolvanen, Pasi; Eränen, Kari; Wärnå, Johan (Frontiers in Chemical Engineering, 2022)
Residence time distribution (RTD) has a very high impact on the performance of a chemical reactor. The development of new reactor and catalyst structures has increased the importance of deep knowledge in theories of RTDs and good experimental practice in measuring RTDs in real systems. Therefore, RTD studies are included in chemical engineering education all over the world. This work demonstrates how RTDs can be measured by using urban pieces of art. Impulse experiments with an inert tracer (NaCl) were conducted in a marvelous modern artwork, ‘Flow of time’ in Turku/Åbo. The results were successfully interpreted with the classical laminar flow model. The application of the methodology in historical university cities is suggested.